ANALISIS PENGGUNAAN MEDIA E-LEARNING BERBASIS WEB BLOG DALAM PEMBELAJARAN SOSIOLOGI - Sari, Tiya; Warneri, Warneri; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe era of modernization at this time affects the types of learning media that exist today. Among them is the existence of web-based blog e-learning media in learning. Media e-learning in the learning process is more or less we find in schools that have adequate facilities and teachers who use them. The research method used is qualitative research with descriptive research methods. The use of web-based blog e-learning media in sociology learning is seen how the planning, implementation, and evaluation of teachers when using web-based blog e-learning media. Planning conducted by the teacher is to prepare the design of the implementation of learning, and the media / methods used in the learning process lesson plans as a guide for teachers in the implementation of learning activities. The blog web is used as a learning medium. Based on research conducted using web-based e-learning media blog in sociology learning, students look easier to understand and convey the material that students have learned. Based on the results of research conducted it can be concluded that the use of e-learning media can be an innovation in learning. In planning, implementing, and evaluating the use of e-learning media. More research needs to be done on the use of web-based e-learning media blogs in learning sociology in schools to see the effectiveness and influence on student motivation and learning outcomes.Â Keywords: Web-based E-learning Blog, Preparation, Implementation, EvaluationÂ